Porzucanie zwierząt jako przestępstwo w polskim porządku prawnym - Polak-Kruszyk, Aleksandra (Zoophilologica. Polish Journal of Animal Studies, 2020)
The article will attempt to show criminal consequences against people who abandon animals according to the Polish law. What is more, the purpose of this paper is to show animal abandonment as one of animal cruelty crimes. In addition, it will systematize applicable penalties taking into consideration Polish criminal law. All in all, it will present animal abandonment according to the Polish civil law, including animals’ legal status in area of property law and movable possessions. To sum up, the article will discuss difficulties which may cause taking of evidence against this kind of criminals, due to actual judicial practice and data of the empirical study.